(untitled) (Archive of Conferences, 2021)
The problem of professional training of engineering students of Jizzakh Polytechnic Institute has been formed. The expediency of synthesizing the three methods is to visualize the learning material using diagrams or tables, to accompany the visual presentation of knowledge with the teacher’s explanations, as well as to solve problems of practical content. It was emphasized that some problems of mechanics should be solved using triple integrals calculated in different coordinate systems. For example, practical problems have been solved by strengthening the knowledge and skills of specialists in the future agro-industrial complex in the development of other fundamental and technical disciplines, as well as in the labor activity in production.